Structural and Electronic Transformations of GeSe2 Glass Under High Pressures Studied by X-Ray Absorption Spectroscopy - Mijit, Emin; Durandurdu, Murat; Rodrigues, Joao Elias F. S.; Trapananti, Angela; Rezvani, S. Javad; Rosa, Angelika Dorothea; Di Cicco, Andrea; Javad Rezvani, S. (Natl Acad Sciences, 2024)
Pressure-induced transformations in an archetypal chalcogenide glass (GeSe2) have been investigated up to 157 GPa by X-ray absorption spectroscopy (XAS) and molecular dynamics (MD) simulations. Ge and Se K-edge XAS data allowed simultaneous tracking of the correlated local structural and electronic changes at both Ge and Se sites. Thanks to the simultaneous analysis of extended X-ray absorption fine structure (EXAFS) signals of both edges, reliable quantitative information about the evolution of the first neighbor Ge-Se distribution could be obtained. It also allowed to account for contributions of the Ge-Ge and Se-Se bond distributions (chemical disorder). The low-density to high-density amorphous-amorphous transformation was found to occur within 10 to 30 GPa pressure range, but the conversion from tetrahedral to octahedral coordination of the Ge sites is completed above similar to 80 GPa. No convincing evidence of another high-density amorphous state with coordination number larger than six was found within the investigated pressure range. The number of short Ge-Ge and Se-Se "wrong" bonds was found to increase upon pressurization. Experimental XAS results are confirmed by MD simulations, indicating the increase of chemical disorder under high pressure.
Mijit, Emin/0000-0002-9232-2538; Trapananti, Angela/0000-0001-7763-5758;
Keywords: Polyamorphism; High Pressure; X-Ray Absorption Spectroscopy; Chemical Disorder